Is there any potential anticancer effect of raloxifene and fluoxetine on DMBA-induced rat breast cancer? - Tatar, Oguzhan; Ilhan, Necip; Ilhan, Nevin; Susam, Solmaz; Ozercan, Ibrahim Hanifi (Wiley, 2019)
Breast cancer is the most common cancer among women in the world and the incidence is increasing alarmingly. It was aimed to determine the effect of raloxifene (RAL) and fluoxetine (FLX) on selected parameters in 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary carcinoma. Thirty-two female Wistar albino rats were assorted into four groups: DMBA (group I), DMBA+RAL (group II), DMBA+FLX (group III), and DMBA+RAL+FLX (group IV). Mammary tissue vascular endothelial growth factor (VEGF), macrophage colony-stimulating factor (M-CSF), matrix metalloproteinase-9 (MMP-9), and tissue inhibitors of matrix metalloproteinase-1 (TIMP-1) levels were determined by the enzyme-linked immunosorbent assay method. The tissue VEGF levels were lower in group IV compared with DMBA group. Decreased M-CSF levels were observed in all therapeutic groups rather than the DMBA group, but the most effective decrease was found in group IV. Compared with the DMBA group, MMP-9 levels were statistically significantly decreased in group II and group IV. However, TIMP-1 levels were higher in the whole therapeutic groups rather than the DMBA group and the most effective increase was observed in group IV. Results of the present study suggest that combined therapy of RAL with FLX might lead to a better outcome targeting breast tumor.
Keywords: breast cancer; DMBA; fluoxetine; raloxifene